Policy Options for Deep Decarbonization and Wood Utilization in California's Low Carbon Fuel Standard - Sanchez, Daniel L.; Fingerman, Kevin; Herbert, Claudia; Uden, Sam (Frontiers in Climate, 2021)
California's Low Carbon Fuel Standard (LCFS) is one of the most important policies to develop and deploy low-carbon and carbon-negative fuels. Yet, because the LCFS is designed to deliver the lowest-cost carbon intensity (CI) reductions possible in the transportation fuel system, it may fail to deliver technologies that would be poised to offer deeper decarbonization or other ancillary benefits to California's people and environment. We contemplate administrative changes to the LCFS to further stimulate the commercialization of promising low-carbon and carbon-negative fuels. To do so, we examine promising technical pathways, their barriers to commercialization, and recent administrative actions by the CA Air Resources Board (ARB) under the LCFS to promote novel lower-carbon fuels. We propose three actions that ARB could undertake to promote commercialization within existing authorities. To commercialize low-carbon and carbon negative fuel, including those derived from forest residue feedstocks, ARB could: (1) embrace the most up-to-date science regarding lifecycle greenhouse gas emissions, (2) create additional, targeted incentives for very low-carbon or carbon-negative fuels through a volumetric technology carve-out or credit multiplier, and (3) ensure that the LCFS stimulates the best-performing fuels across a variety of sustainability parameters.